Modular bioink for 3D printing of biocompatible hydrogels: sol–gel polymerization of hybrid peptides and polymers. Issue 20 (21st February 2017) - Echalier, C.; Levato, R.; Mateos-Timoneda, M. A.; Castaño, O.; Déjean, S.; Garric, X.; Pinese, C.; Noël, D.; Engel, E.; Martinez, J.; Mehdi, A.; Subra, G.
Abstract : Inorganic polymerization as a cross-linking method for 3D printing of PEG–peptide hydrogels. Abstract : An unprecedented generic system allowing the 3D printing of peptide-functionalized hydrogels by soft sol–gel inorganic polymerization is presented. Hybrid silylated inorganic/bioorganic blocks are mixed in biological buffer in an appropriate ratio, to yield a multicomponent bioink that can be printed as a hydrogel without using any photochemical or organic reagent. Hydrolysis and condensation of the silylated precursors occur during the printing process and result in a covalent network in which molecules are linked through siloxane bonds. The viscosity of the colloidal solution used as bioink was monitored in order to set up the optimal conditions for extrusion printing. Grid-patterned hydrogel scaffolds containing a hybrid integrin ligand were printed using a pressure-driven rapid prototyping machine. Finally, they were seeded with mesenchymal stem cells, demonstrating their suitability for cell culture. The versatility of the sol–gel process and its biocompatibility makes this approach highly promising for the preparation of tailor-made cell-laden scaffolds.